THE ANALYSIS OF THE IMPLEMENTATION OF IB SIAGA PENSION FINANCING ACCORDING TO THE DSN-MUI FATWA ON MURABAHAH TAKE OVER AT BANK KB BUKOPIN SYARIAH KPO SALEMBA JAKARTA - Seta Prasetya; Saiful Anwar (EKOSSISTEM : Islamic Economics, Banking, Law, System, 2025)
In the current digital era, the growth of Islamic banking in Indonesia continues to show a significant increase. This research aims to analyze the compliance of the implementation of takeover financing contracts for the iB SiAga Pensiun product at Bank KB Bukopin Syariah KPO Salemba Jakarta with the fatwas of the National Sharia Board - Indonesian Ulema Council (DSN-MUI). Using a descriptive qualitative method with field study and literature review approaches, the research finds that the implementation of the Murabahah bil Wakalah contract used does not substantially meet sharia principles. This contract deviates from the pillars of Murabahah due to the absence of a real commodity object (mabi'), potentially leading to gharar and usury (riba), and is not aligned with the specific schemes formulated by DSN-MUI in Fatwa No. 31/2002 and No. 90/2013. The study recommends product reconstruction by replacing the contract with a hybrid scheme (a combination of Qardh, Sale and Purchase, and Murabahah) for takeovers from Conventional Financial Institutions (LKK) and the Hiwalah bi al-Ujrah scheme for takeovers from other Islamic Financial Institutions (LKS). This should be accompanied by a comprehensive revision of internal guidelines and the strengthening of sharia audits to ensure substantive compliance.